2012
DOI: 10.1108/09526861211198308
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up in head and neck cancer: patients' perspective

Abstract: These data suggest the need for a more patient-focused, individualised approach to follow-up in head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 3 publications
2
28
1
Order By: Relevance
“…Our results are only partially comparable with the studies by Meregaglia et al and Trinidade et al, both of which investigated HNSCC patients' view on follow‐up. The former was conducted at the National Cancer Institute in Milan, Italy, and the latter in three hospitals in London, United Kingdom.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are only partially comparable with the studies by Meregaglia et al and Trinidade et al, both of which investigated HNSCC patients' view on follow‐up. The former was conducted at the National Cancer Institute in Milan, Italy, and the latter in three hospitals in London, United Kingdom.…”
Section: Discussionsupporting
confidence: 87%
“…The survey indicates that many nurses and AHPs are willing to take on a greater role, particularly in the follow-up of 'low-risk' patients. Although medical staff may be reticent about the introduction of alternative models of follow-up, a recent study found that when patients were asked for their views, 73% favoured a less intensive approach in which they could also initiate some visits themselves, and more than half said that they would prefer their first point of contact to be the specialist nurse (Trinidade et al 2012). Furthermore, there is increasing evidence that patients can reliably detect when there is a problem.…”
Section: Figurementioning
confidence: 99%
“…Although several studies have documented the coping strategies adopted by patients with recurrent breast, colon and lung neoplasm (e.g., Mahon & Casperson, ) and by patients with other chronic diseases (Sigstad, Pedersen, & Froland, ; Wahl, Moum, Hanestad, Wiklund, & Kafloss, ; Gulik, ), there is a lack of knowledge of the coping strategies adopted by brain neoplasm patients at both the first occurrence and at recurrence. Knowing the coping strategies adopted by patients and the perceived effectiveness by them helps clinicians to tailor care to individual needs (Trinidade, Kothari, Andreou, Hewitt, & O'Flynn, ; Felder, ; Fitz, ). The primary aim of this study was therefore to contribute to the advancement of knowledge of the coping strategies adopted by brain neoplasm patients on the day before surgical procedure.…”
Section: Introductionmentioning
confidence: 99%